Building Military Doctrine based on History and Experience: 20th century examples from Germany, France, Israel and the US - Przybyło, Łukasz (Eesti Sõjaajaloo Aastaraamat / Estonian Yearbook of Military History, 2019)
The paper will address the role (or lack thereof) of military history and past experience in military doctrine building. The analysis will be based on four case studies: the Reichswehr/Wehrmacht 1919– 1940, the French army 1919–1940, the IDF 1948–1973, and the US Army 1973–1991. In the synthesis, the author will present the role of military history in building efficient military doctrine on three levels of war: tactics, operational art, and strategy. Several kinds of abuses and misuses of military history will be singled out as a warning sign for con- temporary policy and military decision makers.